Ekonomi Token Tanpa Blockchain: Sistem Penghargaan sebagai Perancah Motivasi untuk Penguasaan Kosakata - Rizka Anisa; Maisa Maisa (NAJAHA, 2025)
This study examines gamification strategies centered on Skinner's operant conditioning theory and their impact on learning behavior and student engagement. This strategy focuses on rewards and punishments. Over the course of ten weeks, data were collected via a digital questionnaire distributed to 21 high school students. The questionnaire included open-ended questions to capture qualitative experiences, as well as 5-point Likert scale items to measure perceptions of gamification mechanics. Reflexive thematic analysis, which emphasizes iterative coding and researcher reflexivity, was used to interpret the stories and discover important themes that answer this research question. The main findings showed that while rewards significantly increased external motivation and persistence in completing tasks, technological stress and burnout were caused by technical barriers (such as slow networks and complicated interfaces) and poorly designed competitive elements (such as leaderboards). Students emphasized the importance of balanced gamification, prioritizing intuitive design, collaborative tasks, and consistency with learning objectives. To avoid over-justification, especially given the diverse needs of students, this research emphasizes the importance of combining intrinsic motivation with external rewards